Just institutions matter the moral and political logic of the universal welfare state - Rothstein, Bo. (New York Cambridge University Press, 1998)
In this book Bo Rothstein seeks to defend the universal welfare state against a number of important criticisms that it has faced in recent years. Issues discussed include the relationship between welfare state and civil society, the privatization of social services, and changing values within society. He explains the great variation among contemporary welfare states in terms of differing moral and political logics that have been set in motion by the deliberate choices of political institutions. The book is an important contribution both to philosophical and political debates about the future of the welfare state.
Includes bibliographical references (p. 223-248) and index.
Keywords: Welfare state